THE CORRELATION BETWEEN ENGLISH LEARNERSâ MOTIVATION AND THEIR ENGLISH PROFICIENCY - Ilma, Ridha (English Community Journal, 2018)
This study tried to find out the correlation between motivation and English proficiency of EFL learners. The sample consisted of two hundred and six students of the fourth semester of Law Faculty of Sriwijaya University. This study used correlational study. The instruments to collect the data were questionnaire of English learning motivation and TOEFL Test The result showed that: 1) there was no significant correlation between studentsâ motivation and their English since the significant level (sig. 0.071) was higher than 0.05, 2), studentsâ motivation did not contribute significantly to their English proficiency, the contribution was only 0.2% because the students had different motivation to join English classes. Theresults of this study can be used by lecturers, learners of English, and other concerned parties to concern more about motivation in relation to English proficiency.